-1/9(x-27)+1/3=x+25

Simple and best practice solution for -1/9(x-27)+1/3=x+25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/9(x-27)+1/3=x+25 equation:


x in (-oo:+oo)

(-1/9)*(x-27)+1/3 = x+25 // - x+25

(-1/9)*(x-27)-x+1/3-25 = 0

1/3-1/9*(x-27)-x-25 = 0

(-1/9*3*(x-27))/3+(3*(-x))/3+1/3+(-25*3)/3 = 0

3*(-x)-1/9*3*(x-27)-25*3+1 = 0

1-10/3*x-75+9 = 0

10-10/3*x-75 = 0

-10/3*x-65 = 0

(-10/3*x-65)/3 = 0

(-10/3*x-65)/3 = 0 // * 3

-10/3*x-65 = 0

-10/3*x-65 = 0 // + 65

-10/3*x = 65 // : -10/3

x = 65/(-10/3)

x = -39/2

x = -39/2

See similar equations:

| x^3-8x^2-9x+72=0 | | 138.24=-8(2.3p-4.4) | | [5y+(6x+3)][5y-(6+3)]= | | 8X^4-56x^3+56x^2=0 | | 2(x)-4=5-x | | 8+4(z-2)=-5z+5 | | X^2(X^2-16)-64(X^2-16)=0 | | (1/4^2)-(3/2)-(7/4) | | x(3+7)-5=5(x+4)+5 | | y=8/3*1+8 | | 3r^2-5r-2= | | 1/4^2-3/2-7/4 | | n/7+6=13 | | 4=3x-8-2(5-x) | | t^4+43t^2+42=0 | | r^2-3r+2= | | 3c-12=145c | | 3k^2+-14k+8= | | 3m^2-8m=0 | | -1.6(1+7.6r)=-90.368 | | -7/3=-7/2u-7/5 | | 3(-6+x)=4x-1/3 | | (3x+7/4)+(x+22/5)=9 | | -8*1+7y=-56 | | 5(3m+8)+8(m+4)=95 | | 9d^2+18d+8=0 | | 9a-3a=2a+24 | | 3x+7/4+x+22/5=9 | | (5x-9)(2x+3)= | | t-(9)=4 | | 2x-5+7x=11-3x+4 | | 5(3m+8)+8(m+4)=63 |

Equations solver categories